Development of E-Powerpoint Based Interactive Learning Media in Economics Subjects Viewed from its Efficiency at SMA Negeri 1 Palembang - Riska Putri Fadila; Neta Dian Lestari; Hendri Gunawan (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
The purpose of this research is to develop an interactive economic learning media that can be tested for its efficiency. Method The research used in this research is Rnd (Research and Development) research. which uses the Robert March ADDIE (Analysis, Design, Development, Implement, Evaluate) model. The data collection technique consisted of a questionnaire . The results showed that the economic interactive learning media was declared efficient according to the combined results of the four validators with an average of 95.8% with a very valid category, and judging from the one to one trial with an average of 98.52% with a very valid category. and the small group trial with an average of 97.05% in the very category. So the interactive economic learning media at SMA Negeri 1 Palembang is very feasible to be used as a learning medium.